Ketentuan Hukum Perlindungan Hukum terhadap Hak Kreditur Pemegang Hak Tanggungan atas Tanah yang Menjadi Objek Pengadaan Tanah untuk Kepentingan Umum yang Dananya telah Dititipkan di Pengadilan - Saleem Awud Nahdi; Hasim Purba; Mahmul Siregar (Bulletin of Community Engagement, 2024)
The aim of this research is to analyze the legal provisions for legal protection of the rights of creditors holding mortgage rights over land which is the object of land acquisition for public purposes whose funds have been entrusted to the court. This research uses normative legal research methods with a statutory approach. The research data consists of primary, secondary and tertiary legal materials which were collected using library study techniques and analyzed using qualitative normative data analysis methods. The results of the research and discussion are, the legal position of Mortgage Rights where land is the object of land acquisition as well as legal protection for creditors in land procurement regulations where legal certainty has not been achieved, because there is a legal vacuum that regulates how creditors obtain compensation funds, so it is necessary to add provisions to be able to exercise the right of claim in changes to land procurement regulations so that creditors/banks are involved in the land procurement stages and it is necessary to regulate how the creditor can obtain all or part of the compensation received by the giver of the Mortgage Rights for the repayment of his receivables if the object of the Mortgage Rights is revoked. public interest.